Výpočet vlastních frekvencí prutové soustavy metodou konečných prvků - Svoboda, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2015)
Cílem bakalářské práce bylo naprogramovat algoritmus metody konečných prvků pro výpočet vlastních frekvencí prutových soustav. Pro řešení se mělo primárně využít volně dostupné prostředky (Python, knihovny NumPy, SciPy, překladač Fortranu, apod.) a tím prověřit možnosti volně dostupných prostředků pro vědecké účely v oblasti úloh mechaniky kontinua. Při ověřování funkčnosti programu využít ke srovnání program ANSYS.

The task of the presented bachelor thesis has been to program an algorithm of the finite element method to calculate natural frequencies of beam systems. To solve this problem a freely available SW products (Python, libraries NumPy, SciPy, Fortran compiler etc.) should have been primarily used and thereby to check possibilities of freely available SW product application in science purposes in the field of the Continuum Mechanics tasks. For a functionality verification of the program the ANSYS code is to be used.
Calculation of natural frequencies of a bar system using finite element method
Keywords: Prutová konstrukce; Metoda konečných prvků; Vlastní frekvence; Vlastní tvary; Parametry deformace; Natočení; Posuny; Potenciální energie deformace; Kinetická energie; Hamiltonův princip.; Beam structure; Finite Element Method; Natural frequencies (Eigen frequencies); Eigenvalues; Parameters of deformations; Deflections; Displacements; Potential energy of deformation; Kinetic energy; Hamilton’s principle.